MOTIVATION OF THE ELDERLY AND ELDERLY VISITS TO THE ELDERLY INTEGRATED SERVICE POST (POSYANDU LANSIA) IN KLAMPISAN HAMLET, KEDUNGGEDE VILLAGE, DLANGGU SUB-DISTRICT, MOJOKERTO DISTRICT - Yufi Aris Lestari; Yulianto Yulianto; Aris Hartono; Indrawati Indrawati; Ratna Yunita (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2018)
Background. Having a healthy and prosperous life in old age is the hope of every elderly person. In achieving a healthy and prosperous old age, various efforts have been made by the government, one of which is an Elderly Integrated Service Post (Posyandu Lansia) program.Objectives. This study aims to analyze the relationship of motivation of the elderly and elderly visits to the Elderly Integrated Service Post (Posyandu Lansia) in Klampisan Hamlet, Kedunggede Village, Dlanggu Sub-District, Mojokerto District.Methods. The research design used is analytic cross sectional. The population in this study were all elderly residents of Klampisan Hamlet, Kedunggede Village, Dlanggu Subdistrict, Mojokerto District who had attended the Elderly Integrated Service Post (Posyandu Lansia) as many as 52 people. The sampling technique in the study was simple random sampling. The sample size in this study was 46 people. The measuring instrument used was a questionnaire for motivational variables, and a visit book for elderly visiting to the Elderly Integrated Service Post (Posyandu Lansia) variables.Results. The results showed that the average value of motivation was 68.5870, indicating strong motivation. The average visit value is 1.9348, indicating that the visit is not active. Based on the results of the analysis using the Spearman Rho correlation test obtained ρ = 0.00 <α = 0.05, so that it can be interpreted that there is a relationship between the motivation of the elderly and elderly visits to the Elderly Integrated Service Post (Posyandu Lansia) in Klampisan Hamlet, Kedunggede Village, Dlanggu Sub-District, Mojokerto District.Conclusion. Based on the results of the study showed that there was a relationship between the motivation of the elderly and elderly visits to the Elderly Integrated Service Post in Klampisan Hamlet, Kedunggede Village, Dlanggu Sub-District, Mojokerto District, which could mean that the elderly had strong motivation, then the visit to the Elderly Integrated Service Post would be active. On the contrary, the elderly whose motivation is weak then visit the Elderly Integrated Service Post (Posyandu Lansia) is not active. Keywords: motivation of the elderly, elderly visits, the elderly integrated service post, posyandu lansia